Application of Hots-Based Cognitive Evaluation to Improve Students' Analytical Thinking Skills in Islamic Religious Education - Nurfadhilah; Remiswal; Khadijah (Universitas Negeri Padang, 2025)
PAI learning is currently directed to improve students' critical thinking skills at the HOTS level in understanding PAI materials so that an evaluation that supports the learning direction is needed. Therefore, this study aims to determine the concept of HOTS-based cognitive evaluation in PAI materials and the application of HOTS-based cognitive evaluation in relation to students' thinking skills. This research used a descriptive qualitative approach. Data collection used observation and interview methods. Data analysis techniques using Milles and Huberman models include data reduction, data presentation and conclusion drawing. The results showed that the concept of HOTS-based cognitive evaluation in PAI material includes analysis of learning outcomes, preparation of question grids, making questions and assessment rubrics, covering cognitive aspects C4 analyzing, C5 evaluating and C6 creating, so that in its implementation the application of HOTS-based cognitive evaluation has succeeded in improving students' critical thinking skills and mastery of PAI material well.